Cephalectomy in a HF Crossbred Cow Affected with Dystocia Due to Dicephalus Conjoined Fetal Monster - Sreeranjani, Raju; Selvaraju, Mani; Varudharajan, Venkatraman; Kannan, Mani; Palanisamy, Mahakrishnan; Gopikrishnan, Dorais amy (The Indian Journal of Animal Reproduction, 2026)
A CBHF cow in its third gestation was presented with a history of full-term pregnancy, extended second-stage labor and failure to deliver the fetus. Clinical and per-vaginal examination revealed the presence of a dicephalic fetal monster as the cause of dystocia. Due to the abnormal fetal conformation and failure of traction, cephalectomy was performed to facilitate vaginal delivery of the dicephalic conjoined fetal monster.